Implementation of Mobile Posyandu During Pandemic Covid 19 - Slamet Sholeh; Ani Nurdiani Azizah; Iqbal Amar Muzaki (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
The Indonesian government has decided that the Corona virus desease 2019 (covid 19) as a pandemic disaster. This decision is followed by applying effort to cut off the spreading of the virus through the implementation of social distancing, restricted traveling, isolation, preventing public ocation, closured public services and limiting the using of public facilities. This condition has serious impact on the implementation of public service such as integrated healthcare center (Posyandu), public health center (Puskesmas) and the using of public health facilities as well. Most parents worried and hesitated about to visit Posyandu to do general health check up of their children. And also there are only view employess and administration staffs coming to the office. Some officer and medical staffs also are less. Nevertheless, the goverment (the minister of health) has provided a technical guide to the Puskesmas and Posyandu to run the health activity services during the pandemic, so that the health services that can be done to the children and mother, still can be done by the program of “mobile posyandu”. The study aim to discuss the implementation of posyandu services in the time of pandemic through the operation of mobile posyandu. This study focuses on the services of mobile posyandu and held in 8 different places at Lemah Mulya Village District Majalaya Karawang West Java. The study is using a qualitative method and the data collections is held by holding interviews, observation, focus group discussion (FGD) and litelature study. The result showed that the implementation of mobile Posyandu during the covid 19 pandemic is quite positive and has been done by rescheduling and delivering tasks and duties into each group and each Posyandu volunteer. So that the services of good health for children and mother can stil be done and going on with the strict imposement of health protocol within the pandemic.